PENGARUH SELF EFFICACY DAN LINGKUNGAN KAMPUS TERHADAP PRESTASI AKADEMIK PADA MAHASISWA BIDIKMISI JURUSAN MANAJEMEN FEB UNTAN - admin, Surya Rahman B11112013 (Jurnal Manajemen Update, 2017)
The academic achievement is an entire results which is achieved by a university student in reaching the goals and academic success from the learning efforts. This achievement can be seen from the student’s GPA (Grade Point Average). The academic achievement is influenced by certain factors that are internal and external. The purpose of this research is to find out the influence of self efficacy and campus environment toward the academic achievement of Management students for Bidikmisi program in Economics and Business Faculty at Tanjungpura University. The population of this research is whole students of Management for Bidikmisi program in Economics and Business at Tanjungpura University in Academic Year 2013 – 2015. The total number of populationss for this research are 78 students. Moreover, the samples of this research are 71 students. The sampling technique used in this research is saturated sampling called census. In collecting data, the researcher used primary and secondary data. Furthermore, the researcher also applied double regression analysis as the analysis technique for this research. The final results of this research show that self efficacy and campus environment are influenced positively and significantly toward the academic achievement of Management students for Bidikmisi program in Economics and Business Faculty at Tanjungpura University. The percentage of the result is in the amount of 17.1%. On the other hands, 82% of the result is influenced by the academic achievement of Management students for Bidikmisi program in Economics and Business Faculty at Tanjungpura University. Keywords : Academic Achievement, Self Efficacy, Campus Environment